1998
DOI: 10.1016/s0006-3495(98)77684-2
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Calcium Release in Human Malignant Hyperthermia Muscle Fibers

Abstract: Malignant hyperthermia (MH) results from a defect of calcium release control in skeletal muscle that is often caused by point mutations in the ryanodine receptor gene (RYR1). In malignant hyperthermia-susceptible (MHS) muscle, calcium release responds more sensitively to drugs such as halothane and caffeine. In addition, experiments on the porcine homolog of malignant hyperthermia (mutation Arg615Cys in RYR1) indicated a higher sensitivity to membrane depolarization. Here, we investigated depolarization-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…4A). The actual values varied between 81±6 and 91±2 nM, demonstrating that the cells maintained a low [Ca 2+ ] i similar to that reported earlier for cultured [1,6,8] or adult skeletal muscle fibres [34].…”
Section: Changes In the Calcium Signals During Maturationsupporting
confidence: 84%
“…4A). The actual values varied between 81±6 and 91±2 nM, demonstrating that the cells maintained a low [Ca 2+ ] i similar to that reported earlier for cultured [1,6,8] or adult skeletal muscle fibres [34].…”
Section: Changes In the Calcium Signals During Maturationsupporting
confidence: 84%
“…Higher specific ryanodine binding, indicative of a higher channel open probability and increased sensitivity to activation by micromolar calcium and caffeine was demonstrated in MH-susceptible, p.R615C mutationpositive specimens [Ohta et al, 1989;Mickelson and Louis, 1996]. Four further methods, using tissue prepared from MH-susceptible (MHS) individuals (diagnosed by the in vitro muscle biopsy contracture test [IVCT]) or MHS individuals in which a specific mutation had been identified, have allowed the effects of specific agents on RYR1 channel function to be assessed, but do not allow independent assessment of RYR1 genotype on a controlled background and include analysis of: 1) cultured myotubes [Brinkmeier et al, 1999;Wehner et al, 2002;Wehner et al, 2004;Ducreux et al, 2004]; 2) microsomal SR fractions [Richter et al, 1997]; 3) single muscle fibers [Struk et al, 1998;Duke et al, 2002Duke et al, , 2004; and 4) lymphoblastoid cell lines [Girard et al, 2001;Tilgen et al, 2001].…”
Section: Functional Consequencesmentioning
confidence: 99%
“…Results from functional tests on isolated SR vesicles from MH swine and humans, as well as electrophysiological investigations of reconstituted RYR1 in lipid bilayers, have been somewhat controversial, but in the mutant channels they have identified abnormalities in the channel kinetics for calcium inactivation, hypersensitivity to channel activating ligands such as caffeine and halothane, and hyposensitivity to channel inactivating ligands such as H + , ruthenium red, Mg 2+ and calmodulin [Mickelson and Louis, 1996;Loke and MacLennan, 1998]. Complex studies on excised native muscle fibers from MHS individuals revealed a three-fold increase in the maximal peak rate of calcium release over that for normal muscle, whereas neither kinetics nor voltage dependence of the release were affected [Struk et al, 1998].…”
Section: Biological Relevancementioning
confidence: 99%